Bridging the Gap: Understanding the Barriers to Technical Learning among Adult Learners in Online Distance Education (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This paper presents a comprehensive review of the multifaceted challenges faced by adult learners in internalizing technical learning methods through online distance education. The study uses only secondary data sources and conducts an in-depth investigation of the internal, external, and institutional obstacles that stand in the way of adult learners achieving success in technical education programs. External restrictions, such as work-life balance, caregiving duties, and disruptive home situations, were found to interact with internal obstacles such as cognitive limits, low self-efficacy, and poor self-regulation. These internal barriers were found to interact with external constraints. While this was going on, it was discovered that important drivers to dropout behaviour and low retention consisted of institutional issues connected to outmoded course designs, insufficient learner support services, and a lack of adaptable pedagogical frameworks. The review went on to investigate how these obstacles are connected to one another and frequently compound one another, which ultimately results in disengagement and education cycles that are not completed. The results of studies have shown that adult students who are subjected to external demands are more likely to have increased internal challenges. This is especially true when educational institutions fail to give solutions that are flexible and learner-centred. According to the findings, there is a pressing requirement for integrated support systems that not only target a single category of obstacles, but also the entire ecosystem of learning issues that adult learners face.The article also included a review of global techniques and policy initiatives that have been shown to be effective in countries that have well-established adult education systems. Strengthening institutional capacity, giving training on digital preparedness, building pre-course orientation modules, adopting flexible assessment methods, and guaranteeing continual faculty development are some of the key suggestions that have been extracted from the research that has been conducted. According to the conclusion, there should be legislative changes and methods to online technical education that are attentive to the context, and they should be tailored particularly to meet the varied and ever-changing requirements of adult learners.This research contributes to the ongoing discourse on adult digital education by emphasizing the importance of inclusive, responsive, and technologically progressive strategies to support adult learners in technical domains.